Gêneros textuais no livro didático de língua portuguesa - Bertotti, Karla Simões de Andrade Lima (2012)
This paper seeks to understand how text genres are worked in teaching from the analysis done in Portuguese Language Textbook. Therefore, we update the theoretical discussion of textual genres and their implications for teaching Portuguese language through literature in the reference area. This study was based on proposals by Marcuschi (2008), Sheneulwly & Dolz (2004) and Bronckart (1999), among others, whose attention is focused on the importance of the use of textual genres in the classroom in order to report the student to their daily lives, showing the functionality of language. We seek also to guide our understanding of the object and emphasize the importance of this field, as well as situate the discussion on public policies that have direct consequences in the classroom, including the National Curriculum Parameters of Portuguese Language (NCP) and the National Textbook (NPDB), with specific focus on working with text genres. As a resource for the analysis, we used two collections of textbooks belonging to the same book publisher, comparing their theoretical and methodological approaches in relation to the treatment of text genres. As analysis procedure, we made the presentation of the structure of each chosen LD and the quantitative and qualitative survey of the genres covered in each work. We highlight the relevance of this approach, in order to encourage and develop the participation of the student-reader in communicative practices in society in order to contribute to further research on the use of Textual Genres as a pedagogical tool.